Fast and simple multi-element determination of essential and toxic metals in whole blood with quadrupole ICP-MS - Carmen Silvia Kira, Alice Momoyo Sakuma, Nelson da Cruz Gouveia (Journal of Applied Pharmaceutical Science, 2014)
The development of reliable and sensitive methods for elements quantification in low-level concentration is a necessary requirement to detect increases or deficiencies considered unusual in human body. In this sense the sensitivity and selectivity of mass spectrometric methods are particularly appropriate to deal with this issue since many elements in biological material are at extremely low concentration levels and necessity to be monitored. Simultaneous determination of Be, Bi, Ba, Pb, Pd, Pt, Rh, Ni, V, Cr, Mn, As, Cd, Mo, Co, Hg, Tl, Sr, Sb, Se, Cu and Zn in whole blood by ICP-MS is described. Sample preparation consisted of a simple dilution (twenty-fold) with 0.05% Triton X-100 in 0.2% HNO3. The method proved to be accurate (accuracy ranged from 88.9% to 108%), precise (CV was below 5% for all elements) and sensitive (LOQ were below 1 µg L-1 for most of the studied elements). Use of DRC was only necessary for chromium and vanadium determination in blood. The proposed method uses low quantities of blood and this feature is essential when analyzes involve human biological samples. The obtained results show the applicability of the developed methodology for the rapid, sensitive and simultaneous determination of inorganic constituents in whole blood.
Keywords: Inductively coupled plasma mass spectrometry, ICP-MS, Whole blood, Metals, Validation method.